Chest CT scans are frequently abnormal in asymptomatic patients with newly diagnosed acute myeloid leukemia. Issue 4 (3rd April 2017) - Vallipuram, Janaki; Dhalla, Sidika; Bell, Chaim M.; Dresser, Linda; Han, Heekyung; Husain, Shahid; Minden, Mark D.; Paul, Narinder S.; So, Miranda; Steinberg, Marilyn; Vallipuram, Mayuran; Wong, Gary; et al.
Abstract: Chest computed tomography (CT) findings of nodules, ground glass opacities, and consolidations are often interpreted as representing invasive fungal infection in individuals with febrile neutropenia. We assessed whether these CT findings were present in asymptomatic individuals with acute myeloid leukemia (AML) at low risk of invasive fungal disease. A retrospective study of consecutive asymptomatic adult patients with newly diagnosed AML over a 2-year period was performed at a tertiary care oncology center. Radiology reports of baseline chest CTs were reviewed. Of 145 CT scans, the majority (88%) had pulmonary abnormalities. Many (70%) had one or both of unspecified opacities (52%) and nodules (49%). Ground glass opacities (18%) and consolidations (12%) occurred less frequently. Radiologists suggested pneumonia as a possible diagnosis in 32% ( n  = 47) of scans. Chest CT may result in over-diagnosis of invasive fungal disease in individuals with febrile neutropenia if interpreted without correlation to the patients' clinical status.